Advances in machining & manufacturing technology VIII : selected papers from the 8th Conference on Machining & Advanced Manufacturing Technology in China, November 15-17, 2005, Hangzhou, China - Yuan, Zhejun (Key engineering materials ;, 2006)
This work presents its readers with the most recent advances in the fields of machining and advanced manufacturing technology. It will be of especial valuable to production and research engineers, research students and academics. The current volume contains selected papers from the 8th Conference on Machining & Advanced Manufacturing Technology, held in China. The 182 articles in this collection were selected from the more than 300 extensively peer-reviewed papers submitted to the conference from academia and industry. These particular papers were especially selected because of their authoritative and extensive coverage of the principal themes in this field.